Re-thinking the depictions of two-dimensional ‘living beings’ in contemporary Islamic art / Lina Kattan - Lina Kattan (2015)
This paper principally discusses the religious aspects of Living Being’s representations within Sunni Islamic and Saudi art contexts. It first examines classic Islamic scholars’ visions (conservative and liberal) towards full-figure Living Being depictions, and then compares these visions with their contemporary counterparts. Both classic and contemporary visions tremendously differed. I argue that contemporary Islamic perspectives permitted full-figure representations on two-dimensional surfaces (with some limitations), and at the same time, continued to prohibit three-dimensional depictions. Due to the flatness of the drawn/painted illustration, this study discusses how two-dimensional full-figure Living Beings is no longer sinful as assumed before.